Molecular rotors with designed polar rotating groups possess mechanics-controllable wide-range rotational speed - Jian Shao (Nature Portfolio, 2020)
Abstract Molecular rotors with controllable functions are promising for molecular machines and electronic devices. Especially, fast rotation in molecular rotor enables switchable molecular conformations and charge transport states for electronic applications. However, the key to molecular rotor-based electronic devices comes down to a trade-off between fast rotational speed and thermal stability. Fast rotation in molecular rotor requires a small energy barrier height, which disables its controllability under thermal excitation at room temperature. To overcome this trade-off dilemma, we design molecular rotors with co-axial polar rotating groups to achieve wide-range mechanically controllable rotational speed. The interplay between polar rotating groups and directional mechanical load enables a “stop-go” system with a wide-range rotational energy barrier. We show through density functional calculations that directional mechanical load can modulate the rotational speed of designed molecular rotors. At a temperature of 300 K, these molecular rotors operate at low rotational speed in native state and accelerates tremendously (up to 1019) under mechanical load.